Determinants of the development of corporate bond markets in Argentina: Survey to firms and investors - María Alegre; Sergio Pernice; Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2007)
Conventional theory leads to expect bonds to be a financing vehicle for large firms because of economies of scale and contracting costs. In this paper we present the results for Argentina of a survey of firms and of investors on the use of corporate bonds. The result of these surveys supports the idea that for Argentine firms, bonds are a financing vehicle of choice only for firms above a certain (large) size. This is independent of the criteria used for firm size. This result is similar to results in other countries such as the United Sates.
Keywords: G3; E6; 330; debt structure; leverage; short-term debt; corporate bonds; firm size; firm value; Kapitalstruktur; Argentinien